Small cavity creation in the vertebral body reduces the rate of cement leakage during vertebroplasty. Issue 1 (9th March 2016) - Arabmotlagh, Mohammad; Rickert, Marcus; Lukas, Alexander; Rauschmann, Michael; Fleege, Christoph
ABSTRACT: Cement leakage is the most common complication during vertebroplasty and may result in serious morbidity. Measures to reduce the rate of cement leakage are valuable ways to improve vertebroplasty safety. The present study aimed to evaluate whether creating a small cavity in the vertebral body prior to cement injection would reduce the rate of cement leakage during vertebroplasty. The study included 36 consecutive patients with 42 painful osteoporotic vertebral body compression fractures that were classified as A1 fractures according to AO classification. Patients were randomly assigned to receive either treatment with vertebroplasty (control) or with a procedure termed cavuplasty, in which a small cavity was created in the vertebral body prior to cement injection. CT scanning was performed to detect cement leakage. Cement leakage was observed in 14 (66.6%) of the 21 vertebral bodies treated with vertebroplasty and 5 (23.8%) of the 21 vertebral bodies treated with cavuplasty ( p = 0.012). These results suggest that the creation of a small cavity in the vertebral body prior to cement injection is an effective way to reduce cement leakage during vertebroplasty. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:154–159, 2017.